Ag3PO4/Ag nanocomposite for selective and sensitive cyanide determination in food samples through catalytical colorimetry using a paper-based test kit - Nutthaporn Malahom (2022)
A paper-based test kit for selective and sensitive determination of cyanide was successfully developed using a Ag3PO4/Ag nanocomposite for catalytic colorimetry. The Ag3PO4/Ag nanocomposite synthesized via a one-step chemical bath method could instantly oxidize the chromogenic substrate ABTS for the color development under acidic conditions without the requirement of H2O2. During the detection step, cyanide in the sample was converted into gaseous hydrogen cyanide (HCN) using sulfuric acid. The HCN species then reacted with the generated Ag+ species via coordinate covalent bonding to form silver cyanide complex ions [Ag (CN2)]-. The amount of Ag+ species used for oxidizing ABTS subsequently decreased and so did the color intensity on the paper-based test kit. Specifically, the color intensity decreased with increasing cyanide concentrations in the range of 2.50–20.0 mg L−1. The limit of detection (LOD) and limit of quantification (LOQ) were 0.48 mg L−1 and 1.59 mg L−1, respectively. The developed test kit showed relatively high selectivity towards cyanide and high tolerance towards other cations and anions present in real samples. When applied to real samples including fruit juices and food products, the performance of the rapid and low-cost test kit was well validated by a conventional precipitation titration method.﻿